Effects of Annealing Soaking Time on Carbide Precipitates and Mechanical Properties of As-Cast Thin Wall Ductile Iron - Ochulor, Ezenwanyi Fidelia; Adeosun, Samson Oluropo; Kareem, Ademola Joseph; Ashade, Ajibola Ikeoluwa (ABUAD Journal of Engineering Research and Development (AJERD), 2023)
Thin Wall Ductile Irons (TWDI) are viable material option in the automotive industry due of their good castability, adequate mechanical properties, wear resistance, good machinability and fatigue properties. However due to size reduction and increased cooling rate, carbide precipitates occur in the as-cast microstructure of TWDIs, impacting negatively on mechanical properties, nodularity and nodule count. Heat treatment processes that reduce or eliminate these carbide phases can be adopted to remedy such defects. In this study, 4 mm TWDI samples cast in green sand moulds, showing carbide precipitation in microstructure were subjected to an Annealing heat treatment by austenizing to 920oC and varying soaking times of 5, 10, 15, 20, 25 and 30 minutes, afterwards they were cooled in the furnace to room temperature. Microstructural analysis and mechanical property tests were carried out in all the samples via Optical microscopy (OM) and Scanning electron microscopy (SEM), hardness and tensile tests. Microstructure of heat-treated samples showed significant reduction of carbide precipitates in comparison with their as cast counterpart. It was observed that the soaking time impacted on carbide precipitation reduction. Hardness values reduced from 291.6 Hv in the as cast sample to 247.8 Hv and 243.5 Hv for samples soaked for 25 and 30 minutes respectively, whereas tensile strength reduced progressively from 596 MPa to 544 MPa for as cast to 30 minutes soaking time respectively. Percent elongation increased from 4.3 % elongation for the as cast sample to 8.7 % elongation in the sample with soaking time of 30 minutes at 920 oC. This study has shown that carbide precipitation can be significantly reduced by adopting the annealing treatment parameters outlined above.